Factors influencing the discontinuation of biologic therapies in patients with ulcerative colitis - Arisa Fukuyama; Akio Nakashima; Motoyasu Miyazaki; Masakatsu Fujiki; Hideki Kakimoto; Takashi Hisabe; Osamu Imakyure (BMC, 2024)
Abstract Background The therapeutic landscape for ulcerative colitis (UC) has recently broadened to include anti-TNFα, anti-integrin, and anti-IL-12/23p40 antibody agents. These biological agents are tailored to individual patient profiles. However, some patients cease biological treatment. This study investigates factors influencing the discontinuation of biological treatment in UC patients. Methods This retrospective single-cohort study encompasses UC patients who commenced treatment with biological agents like infliximab, adalimumab, golimumab, vedolizumab, and ustekinumab from April 2019 to March 2022. Patients were categorized into continuation and discontinuation groups based on their one-year treatment status. Baseline characteristics were compared between the groups. Results Of the 116 UC patients, 102 were included in the study. Among these, 74 (72.5%) continued and 28 (27.5%) discontinued biological therapy. Discontinuation rates for infliximab, adalimumab, golimumab, vedolizumab, and ustekinumab were 33.3%, 25.0%, 50.0%, 30.2%, and 15.6%, respectively. The primary discontinuation reason was lack of efficacy (85.7%), followed by adverse events (7.1%), pregnancy (3.6%), and death (3.6%). The discontinuation group had a significantly lower rate of concomitant thiopurine compared to the continuation group (28.6% vs. 56.8%, p = 0.0132). Multivariable analysis revealed that concomitant thiopurine was independently associated with therapy continuation (p = 0.0075). Conclusion The study indicates that concomitant thiopurine significantly correlates with the continuation of biological therapies in UC patients, underscoring the importance of concomitant thiopurine in sustaining biological therapy. Further studies are warranted to assess the efficacy of combination therapy.